Evaluation of transthoracic fine-needle aspiration biopsy effectiveness under control of fluoroscopy with a use of X-ray unit with C-arm in diagnostics of lung cancer - Jahnz-Różyk, Karina; Włodarczyk, Robert (Contemporary Oncology/Współczesna Onkologia, 2001)
Transthoracic fine-needle aspiration biopsy (TFNAB) is recognized diagnostic method for lung cancer. In Military Hospital of Tuberculosis and Lung Diseases in Otwock this procedure is carried out with use of X-ray unit with C-arm. This study was designed to evaluate the use of TFNAB in diagnosis of lung cancer. 330 patients aged 21–84 years were enrolled in the study. There were 400 procedures of TFNAB done in this group. The statistic analysis was carried out in 193 patients, in which the lung cancer was diagnosed with TFNAB and the group of 29 patients with negative TFNAB, in which the lung cancer was recognized with use of other methods. Aim of the study was: evaluation of TFNAB use in the lung cancer diagnosis on the bases of: sensitivity of the method for chosen characteristic of the patient with lung tumor designation of the parameters, which significantly influence the diagnostic efficiency of TFNAB. The sensitivity of the method for each diagnosis in comparison to designated parameters was designated in statistical analysis. There was also completed discriminative analysis, which was to point out the parameters that enable foreseeing the efficiency of TFNAB in the lung cancer diagnostic. It was shown that the highest sensitivity of the method can be seen for the parietal lung cancer, with silent contour in classical X-ray, located in the right lung, with 65–95 mm diameter, in the men aged over 63 years. The parameters, which significantly influence the diagnostic efficiency of TFNAB are: age of patient, tumors diameter, tumors contour, tumors localization in the right lung.